Restricting dietary sodium reduces plasma sodium response to exercise in the heat - Koenders, E. E.; Franken, C. P. G.; Cotter, J. D.; Thornton, S. N.; Rehrer, N. J. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Exercise-associated hyponatremia can be life-threatening. Excessive hypotonic fluid ingestion is the primary etiological factor but does not explain all variability. Possible effects of chronic sodium intake are unknown. The aim of this study was to determine whether dietary sodium affects plasma sodium concentration [Na+] during exercise in the heat, when water intake nearly matches mass loss. Endurance-trained men (n = 9) participated in this crossover experiment. Each followed a low-sodium (lowNa) or high-sodium (highNa) diet for 9 days with 24-h fluid intakes and urine outputs measured before experimental trials (day 10). The trials were =2 week apart. Trials comprised 3 h (or if not possible to complete, to exhaustion) cycling (55% VO2max; 34 °C, 65% RH) with water intake approximating mass loss. Plasma [Na+], hematocrit, sweat and urine [Na+], heart rate, core temperature, and subjective perceptions were monitored. Urine [Na+] was lower on lowNa 24 h prior to (31 ± 24, 76 ± 30 mmol/L, P = 0.027) and during trials (10 ± 10, 52 ± 32 mmol/L, P = 0.004). Body mass was lower on lowNa (79.6 ± 8.5, 80.5 ± 8.9, P = 0.03). Plasma [Na+] was lower on lowNa before (137 ± 2, 140 ± 3, P = 0.007) and throughout exercise (P = 0.001). Sweat [Na+] was unaffected by diet (54.5 ± 40, 54.5 ± 23 mmol/L, P = 0.99). Heart rate and core temperature were higher on lowNa (P = 0.001). Despite decreased urinary sodium losses, plasma sodium was lower on lowNa, with decreased mass indicating (extracellular) water may have been less, explaining greater heart rate and core temperature. General population health recommendations to lower salt intake may not be appropriate for endurance athletes, particularly those training in the heat.